Dialektika Budaya Toraja dan Inklusifitas Pendidikan Agama Kristen dalam Masyarakat Majemuk - Sanderan, Rannu; Ua' Tandi Pau', Jhon (Institut Agama Kristen Negeri Toraja, 2025)
Abstract: This study examines the intersection of Toraja traditions and Christian religious education within Indonesia's pluralistic context. By analyzing the inclusive values and harmony inherent in Toraja culture, it underscores its relevance as a model for interreligious tolerance. The research adopts a qualitative approach, utilizing in-depth interviews, participatory observation, and document analysis to gather data. This methodology allows for a comprehensive exploration of how Christian religious education in Toraja integrates cultural traditions with religious teachings. The study shows how the adaptation of Christian education in the multicultural setting of Toraja fosters mutual respect, social cohesion, and the integration of cultural and religious identities. This approach highlights the strategic role of education in promoting peaceful coexistence and inclusivity, providing valuable insights into the interaction between tradition, religion, and modern pluralistic society. Keywords: Christian religious education; interreligious tolerance; multicultural integration; pluralistic society; Toraja Abstrak: Penelitian ini menganalisis persinggungan antara tradisi Toraja dan pendidikan agama Kristen dalam konteks pluralisme Indonesia. Dengan mengkaji nilai-nilai inklusivitas dan harmoni yang terkandung dalam budaya Toraja, penelitian ini menyoroti relevansinya sebagai model toleransi antaragama. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif, dengan mengumpulkan data melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Metode ini memungkinkan eksplorasi mendalam mengenai bagaimana pendidikan agama Kristen di Toraja mengintegrasikan tradisi budaya dengan ajaran agama. Penelitian ini menunjukkan bagaimana adaptasi pendidikan Kristen dalam lingkungan multikultural Toraja memperkuat penghormatan, kohesi sosial, dan integrasi identitas budaya serta keagamaan. Pendekatan ini menekankan peran strategis pendidikan dalam mendorong ko-eksistensi damai dan inklusivitas, memberikan wawasan penting mengenai interaksi antara tradisi, agama, dan masyarakat majemuk modern. Kata kunci: Pendidikan agama Kristen; toleransi antaragama; integrasi multibudaya; masyarakat majemuk; tradisi Toraja